Atypical histopathological presentation in bone marrow of multiple myeloma - Aliaga-Chávez, Rolig A. (2022)
Objetive: To describe the atypical histopathologic presentation in bone marrow of multiple myeloma. Case Report: We present the case of a 75-year-old male who manifested low back pain of variable intensity associated with decreased urinary flow, for which he went to the emergency room. On physical examination, vital functions were within normal parameters with generalized decrease in adipose tissue and earthy pallor, the rest of the examination being non-contributory. Bone marrow studies showed 13% of plasma cells with tetranucleated neoplastic cells with 1 and 2 nucleoli, basophilic cytoplasm with presence of vacuoles, which was corroborated in flow cytometry with pathological phenotype in relation to plasma cell neoplasia. The patient receives a therapeutic regimen with cyclophosphamide, dexamethasone and thalidomide. Conclusion: Tetranucleated presentation is a rare histopathologic variant of multiple myeloma, so this peculiar finding should be appreciated in the microscopic diagnosis of this clinical entity.